Functional impact of IGHG3 genetic variation in HIV-1 infection - Spencer, Holly (My University, 2022)
IgG3 antibodies are able to mediate a broad range of potent Fc effector functions. Several of which have been associated with reduced risk of infection following HIV vaccination. Furthermore, IGHG3 (the gene encoding IgG3) contains the highest level of reported allelic diversity, with 29 documented alleles in the international immunogenetics database (IMGT). While there is some evidence that key IgG3 mutations can alter antibody half-life and effector function, the functional impact of these alleles is generally poorly characterized. Additionally, the diversity of IGHC genes has not been investigated in Southern African populations. The aim of this project was to sequence the full-length IGHG3 in the CAPRISA cohort and to test their functional relevance in the context of HIV. Using Sanger and PacBio platforms, five novel IGHG3 alleles were identified, three of which contained amino acid substitutions in coding regions. A further ten documented alleles were identified from nine participants. The alleles identified were used to clone participant-matched HIV-specific antibodies previously isolated from the nine individuals sequenced, alongside IgG1*01 and IgG3*01 controls. The ability of these antibodies to induce antibody-dependent cellular phagocytosis (ADCP), to neutralize, to bind to FcγRIIA; and their susceptibility to protease digestion was tested. Overall, IgG3 antibodies exhibited equivalent or enhanced ADCP, neutralization and FcγRIIA-binding compared to IgG1 antibodies, while the functional differences between IGHG3 alleles were subtle. This was observed across multiple strain-specific and broadly neutralizing antibodies targeting various HIV epitopes. Altogether, we found a high level of genetic diversity in a small sample-size, motivating for further investigation into IGHG3 diversity within understudied populations. The outcomes of this project contribute to our understanding of how genetic diversity affects function in IgG3 antibodies, in line with a growing body of research supporting the use of IgG3 antibodies in passive immunization for HIV prevention.
A Dissertation submitted in fulfilment of the requirements for the degree ofMaster of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2022